1988
DOI: 10.1128/iai.56.12.3201-3208.1988
|View full text |Cite
|
Sign up to set email alerts
|

Specific and nonspecific inhibition of adhesion of oral actinomyces and streptococci to erythrocytes and polystyrene by caseinoglycopeptide derivatives

Abstract: Various caseinoglycopeptide derivatives prepared from mammalian milk were evaluated as inhibitors of hemagglutinations mediated by Actinomyces viscosus Nyl, Streptococcus sanguis OMZ9, and, for comparative purposes, plant lectins from Arachis hypogaea and Bauhinia purpurea. It was found that recognition of the * Corresponding author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…These polypeptides of tnilk origin prevetited the adhesion of the test streptococci to S-HA, whereas the satne compounds did not interfere with the ability of A. viscosus Ny 1 to bind to S-HA. Thus, the inhibitory properties of these tnilk casein derivatives appear to be restricted to the streptococcal strains studied and are therefore clearly distinct from those of other inhibitors of microbial adhesion to nonbiological surfaces, such as BSA and PEG (39,43). The effect of these casein derivatives is not specifically mediated by phosphate groups or by terminal sialic acid residues.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These polypeptides of tnilk origin prevetited the adhesion of the test streptococci to S-HA, whereas the satne compounds did not interfere with the ability of A. viscosus Ny 1 to bind to S-HA. Thus, the inhibitory properties of these tnilk casein derivatives appear to be restricted to the streptococcal strains studied and are therefore clearly distinct from those of other inhibitors of microbial adhesion to nonbiological surfaces, such as BSA and PEG (39,43). The effect of these casein derivatives is not specifically mediated by phosphate groups or by terminal sialic acid residues.…”
Section: Discussionmentioning
confidence: 89%
“…In a previous study we have shown that, after desialylation, CGP behaved as a potent and specific inhibitor of hemagglutinations mediated by Actitwmyces viscosus Ny 1 (39). Also, both native and desialylated variants of CGP totally, but nonspecifically, prevented the adhesion of oral actinomyces and streptococci to polystyrene surfaces (39). Along with the in vivo results of Reynolds et al (41,42), these //; vitro data prompted us to investigate the eflects of bovine milk casein and CGP derivatives on the adhesion of test strains of/I.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated that the non-immunoglobulin fraction of HM may inhibit bacterial adhesion (1,2,3,8,10). This effect may, at least in part, be due to the presence of analogues of specific epithelial receptors for microorganisms (free oligosaccharides, glycoproteins) (1,3).…”
Section: Resultsmentioning
confidence: 97%
“…1. HM has also been shown to exert anti-adhesive effects on certain Escherichiu coli strains ( 3 , S), Streptococcus pneumoniae and Haemophilus influenzae (1,2), and oral Actinomyces and streptococci (10).…”
Section: Resultsmentioning
confidence: 99%